Budaya Pondok Pesantren YAMISA Soreang Bandung dalam Membangun Kemandirian Karakter Santri - Saparudin, Hery (Asosiasi Mahasiswa Program Pascasarjana | Institut Agama Islam Darussalam | IAID | Ciamis | Jawa Barat, 2018)
Pesantren is basically a traditional Islamic education where the students lived with and studied under the guidance of one (or more) teachers are better known as kyai. Although pesantren was considered traditional, but still exist and survive in modern age and global era. Obviously because this institution has its own characteristics and maintain institutional elements that have formed since former. The characteristics of education in pesantren classified to two: (1) the general pattern of education, which are pesantren institutions introducing levels, from that teach simple texts until sublime pesantren that teach high level texts. (2) Teaching systems are the sorogan system and bandongan system. As for the institutional elements in pesantren are cottage, mosques, students, kyai, classical Islamic books